Nano-optomechanical characterization of surface-plasmon-based tunable filter integrated with comb-drive actuator. (10th February 2017) - Honma, H; Mitsudome, M; Ishida, M; Sawada, K; Takahashi, K
Abstract: We report a tunable plasmonic color filter consisting of a metamaterial periodic grating and microelectromechanical systems (MEMS) actuator. An aluminum subwavelength grating is integrated with electrostatic comb-drive actuators to expand the metal subwavelength period, which allows continuous control of the excitation wavelength of surface plasmons (SPs). We develop a batch fabrication process by employing a liftoff technique using an electron beam resist altered by the electron dose depending on different aspect ratios (length/width) for various components such as the subwavelength grating, nanohinge flexural suspensions, and comb fingers. We successfully demonstrate a continuous shift in the excitation wavelength over the 514–635 nm range by nanopitch expansion. The design margin of the grating period for SP excitation is evaluated by comparing the experimental pitch variation and theoretically calculated values. The resonance frequency of the tunable filter is optically measured to be approximately 10 kHz. The optically and mechanically obtained values agree well with the theory of electrostatic actuation and finite-difference time-domain simulation.